2010
DOI: 10.1111/j.1468-2311.2010.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Prison Guards' Attitudes Towards the Prevention of Sexual Contacts Between Inmates

Abstract: This article presents the main findings of an innovative Portuguese research project on prison guards' attitudes towards the prevention of sexual contacts between inmates. Sexuality in prisons is still a poorly-studied issue, although its increasing visibility demands a better understanding of prison dynamics. Results show that guards hold very favourable attitudes towards the prevention of forced sexual contacts between inmates, but they are more ambiguous concerning consensual sexuality. This result is influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
2
Order By: Relevance
“…For instance, studies conducted in a Spanish prison found a relationship between sexual satisfaction and psychological health (Carcedo, López, Orgaz, Toth, & Fernández-Rouco, 2008;Carcedo et al 2014), indicating the importance of sexual fulfilment for prisoner wellbeing. Knowledge about how sexuality is experienced and expressed in prison is needed to ensure the sexual health of prisoners (Coelho & Gonçalves, 2010).…”
Section: A Neglected Area Of Researchmentioning
confidence: 99%
“…For instance, studies conducted in a Spanish prison found a relationship between sexual satisfaction and psychological health (Carcedo, López, Orgaz, Toth, & Fernández-Rouco, 2008;Carcedo et al 2014), indicating the importance of sexual fulfilment for prisoner wellbeing. Knowledge about how sexuality is experienced and expressed in prison is needed to ensure the sexual health of prisoners (Coelho & Gonçalves, 2010).…”
Section: A Neglected Area Of Researchmentioning
confidence: 99%
“…For instance, studies conducted in a Spanish prison found a relationship between sexual satisfaction and psychological health (Carcedo et al, 2008; Carcedo et al, 2014), indicating the importance of sexual fulfillment for inmate well-being. Knowledge about how sexuality is experienced and expressed in prison is needed to ensure the sexual health of prisoners (Coelho & Gonçalves, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Existing sociological research on prisons acknowledges gender, sex, and sexuality as socially constructed aspects of individuals’ lives that reflect larger social forces and are organized differently based on the differential contexts in which individuals’ lives are situated. Classic research on gender, sex, and sexuality in prisons has focused primarily on inmate and staff attitudes toward sex and sexuality (Alarid 2000; Blackburn et al 2011; Coelho and Goncalves 2010; Eigenberg 2000; Hensley and Tewksbury 2005); sexual health, particularly the threat of HIV/AIDS as a result of sexual behavior in prison (Blumberg 1989; Stewart 2007); and sexual coercion, rape, and victimization within the prison environment (Chonco 1989; Knowles 1999; Man and Cronan 2001; Struckman-Johnson et al 1996; Struckman-Johnson and Struckman-Johnson 2006; Wolff, Shi, and Bachman 2008). Studies have also examined consensual sex within male (Hensley 2001; Hensley, Tewksbury, and Wright 2001; Saum et al 1995; Tewksbury 1989; Wooden and Parker 1982) and female (Hensley, Tewksbury, and Koscheski 2002; Otis 1913; Owen 1998; Ward and Kassebaum 1965) prisons, particularly in relation to the prevalence of consensual same-sex behavior.…”
mentioning
confidence: 99%